Pemanfaatan Big Data dan AI untuk Smart Decision Making dalam Manajemen SDM - Yamin, Muhammad (Journal of Current Research in Humanities, Social Sciences, and Business, 2025)
The development of digital technology has driven organizations to integrate Big Data and Artificial Intelligence (AI) into human resource (HR) management. The use of these technologies has shifted decision-making paradigms from intuition-based approaches to data-driven ones that are more accurate, fast, and objective. This study aims to analyze the role of Big Data and AI in supporting smart decision-making in HR management through a literature review. The method applied is a systematic review of relevant scholarly journals, books, and industry reports published between 2015 and 2024. Thematic analysis was conducted to identify patterns of utilization, benefits, and implementation challenges. The findings show that Big Data plays a role in processing massive information covering the entire employee lifecycle, while AI provides predictive and prescriptive analytics that generate strategic recommendations. The integration of both technologies has proven effective in improving recruitment, performance appraisal, workforce planning, and employee retention. However, the implementation of these technologies still faces challenges such as algorithmic bias, data privacy, and infrastructure limitations. Therefore, ethical, transparent, and gradual implementation strategies are necessary to optimize the benefits of these technologies.